2015
DOI: 10.1039/c5cp00637f
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy-induced initial decomposition of condensed phase NTO via bimolecular hydrogen transfer mechanisms at high pressure: a DFT-D study

Abstract: Density functional theory with dispersion-correction (DFT-D) was employed to study the effects of vacancy and pressure on the structure and initial decomposition of crystalline 5-nitro-2,4-dihydro-3H-1,2,4-triazol-3-one (β-NTO), a high-energy insensitive explosive. A comparative analysis of the chemical behaviors of NTO in the ideal bulk crystal and vacancy-containing crystals under applied hydrostatic compression was considered. Our calculated formation energy, vacancy interaction energy, electron density dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 62 publications
1
11
0
2
Order By: Relevance
“…The distribution of the frontier energy levels reveals the activity of HMX molecules at the internal and external surface. This is in good agreements with previous studies that the surfaces in HMX (crystal surfaces, 4-6 internal vacancies, 3,36,37 and voids 2 ) promote the chemical decomposition of energetic materials. Their studies indicate that the chemical decompositions are more likely to start on the inner and outer surfaces.…”
Section: Electronic Structuressupporting
confidence: 93%
“…The distribution of the frontier energy levels reveals the activity of HMX molecules at the internal and external surface. This is in good agreements with previous studies that the surfaces in HMX (crystal surfaces, 4-6 internal vacancies, 3,36,37 and voids 2 ) promote the chemical decomposition of energetic materials. Their studies indicate that the chemical decompositions are more likely to start on the inner and outer surfaces.…”
Section: Electronic Structuressupporting
confidence: 93%
“…The thermal-induced decomposition kinetic process and burning characteristics of NTO [ 6 , 7 , 8 , 9 , 10 , 11 ] have been studied via various experimental techniques. In addition, the theoretical works concerning the electron structures and possible decomposition paths of NTO [ 12 , 13 , 14 ] were also reported. However, the atom-scale understanding about the shock-induced chemistry reaction of NTO still remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in theoretical and experimental approaches have made people obtain abundant information about the roles of the surfaces (external surfaces, interfaces, and internal surfaces such as vacancies, voids, etc.) in the decompositions of the energetic materials. ,, For example, previous ab initio studies presented activation energy and kinetics of decomposition reactions at the surface and internal vacancies for the β- and δ-HMX crystals. , These results confirmed that the surface and vacancy in the bulk altered their decomposition kinetics and mechanisms. Sharia and Kuklja found that the N–NO 2 homolysis of the HMX molecule on the surfaces of β-HMX requires lower activation energy and progresses with an orders of magnitude faster reaction rate than that in the bulk crystal.…”
Section: Introductionmentioning
confidence: 67%